"Спалитися в безупиннім життю..." (Юрій Липа): шоста лекція на пошану першого ректора в Огієнковому університеті - Рарицький, Олег (Іван Огієнко і сучасна наука та освіта, 2022)
On October, 22, on the occasion of the 102-nd anniversary of the founding of Kamianets-Podіlskyi National Ivan Ohiienko University, the II All-Ukrainian Scientific Conference «Traditions of Ivan Ohiienko in the light of national science» took place. During the conference, Professor of Izmail State University of Humanities Halyna Raibedyuk gave an open lecture on the subject: «Spalytysia v bezupynnim zhyttiu: a passionary energy of the word and rank of Yuri Lypa». The lecture was a continuation of a series of annual readings, dedicated to the memory of the fi rst rector of Kamianets-Podіlskyi National Ivan Ohiienko University, as well as famous writers of Podillia. The lecture is dedicated to the 120-th anniversary of the birth of the passionarist of the Ukrainian people Yuri Lypa – a unique writer, a passionate publicist, one of the leading theorists of state formation, a leading ideologue of the latest allUkrainian worldview of the interwar decade. The materials, presented in the lecture and during the discussion about the year in Kamianets in the life of Yuri Lypa (1919-1920), were of particular interest by a student of Kamianets-Podіlskyi National Ivan Ohiienko University, as well as the materials about the relief «footprint» of Kamianets as the epicenter of the liberation struggle. In his subsequent biography, which infl uenced the passionary energy of ascetic activity – from impulse and rank to martyrdom.